2019
DOI: 10.1186/s12885-019-6034-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of ex vivo-expanded natural killer cell-enriched lymphocytes (MYJ1633) against liver cancer

Abstract: Background Adoptive transfer of immune cells such as T cells and natural killer (NK) cells has emerged as a targeted method of controlling the immune system against cancer. Despite their significant therapeutic potential, efficient methods to generate adequate numbers of NK cells are lacking and ex vivo-expansion and activation of NK cells is currently under intensive investigation. The primary purpose of this study was to develop an effective method for expansion and activation of the effector ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, the scarcity of NK cells in human lymphocytes, their changing phenotype, and their impaired functionality during cancer progression necessitates the development of protocols to activate and expand NK cells to sufficient numbers ex vivo for adoptive transfer [4,5]. We have developed a feeder-free NK cell expansion system where clinically viable NK cells are isolated and cultured from human peripheral blood mononuclear cells (PBMCs) for NK studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the scarcity of NK cells in human lymphocytes, their changing phenotype, and their impaired functionality during cancer progression necessitates the development of protocols to activate and expand NK cells to sufficient numbers ex vivo for adoptive transfer [4,5]. We have developed a feeder-free NK cell expansion system where clinically viable NK cells are isolated and cultured from human peripheral blood mononuclear cells (PBMCs) for NK studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that survival and prognosis of HCC patients is positively correlated with NK cell numbers in blood and tumour tissue (169). Tumour progression of these HCC patients was associated with dysfunction of the tumour-infiltrating NK cells (170), and exhausted tumour-infiltrating NK cells correlate with poor clinical outcome for HCC patients. Importantly, this NK cell exhaustion was reversed by manipulating the TIGIT pathway (171).…”
Section: The Potential For Future Combination Immunotherapy In Hcc Checkpoint Therapy To Enhance T and Nk Cell Functionmentioning
confidence: 99%
“…Autologous NK adoptive immune cells are obtained by stimulating the in vitro expansion of CD56 Birght NK cells in peripheral monocytes with cytokines. NK cells in peripheral blood can proliferate 140 times in a short time by stimulating with some cytokines ( 114 ). Meanwhile, these amplified and activated NK cells show strong anti-tumor effects in vitro and in vivo ( 114 ).…”
Section: The Immunotherapy Of Hccmentioning
confidence: 99%
“…NK cells in peripheral blood can proliferate 140 times in a short time by stimulating with some cytokines ( 114 ). Meanwhile, these amplified and activated NK cells show strong anti-tumor effects in vitro and in vivo ( 114 ). Nonetheless, the clinical efficacy of autologous NK cells is not significant ( 115 ).…”
Section: The Immunotherapy Of Hccmentioning
confidence: 99%